Incidence of Allergy to Antibiotics During the Period Of 2019-2020- A Retrospective Study - AHMED M, ASHFAQ; O. R, HEMAVATHY; DINESH, S.P. SARAVANA (The journal of contemporary issues in business and government, 2020)
The prescribing of antibiotics by dental practitioners has become an important aspect of dental practice. For this reason, antibiotics account for the vast majority of medicines prescribed by dentists. Allergy to antibiotics is a rare phenomenon which can occur from any group of drugs, such drugs should be avoided as possible and alternative drugs should be prescribed. The aim of the study is to analyse the incidence of antibiotic allergy during 2019-2020. Evaluation of 126 reports of patients reported to saveetha dental college and hospitals were analysed and the results were statistically analysed and tabulated using chi square test. intraoperative photographs were checked for cross verification. Out of 126 subjects, in the age group of 1-30 years, 15 patients(11.90%) were allergic to antibiotics and 21 patients(16.67%) were clinically healthy and in the age group of 31-60 years, 39 patients(30.95%) were allergic to antibiotics and 36 patients (28.57%) were clinically healthy. and in the age group of 61-80 years, 7 patients(5.56%) were allergic to antibiotics and 8 patients (6.35%) were clinically healthy. Among the 126 patients, 64 patients were males in which 33 patients were allergic to antibiotics(26.19%%) and 31 patients were healthy(24.60%). 62 patients were females in which 28 patients were allergic to antibiotics(22.22%) and 34 patients were healthy(26.98%) and the results obtained were statistically insignificant (P>0.05). Within the limits of this study of antibiotic allergy, incidence in males were higher and majority of the patients of the age group of 31- 60 years were allergic to antibiotics.